The subgenera Calhyboma, Hybomidium, and Telhyboma (Coleoptera: Scarabaeidae: Scarabaeinae: Deltochilum) in Colombia - GONZÁLEZ-A., FABIO ARTURO; MOLANO-R., FREDY; MEDINA-U., CLAUDIA ALEJANDRA (Revista Colombiana de Entomología, 2009)
A total of 897 specimens of the genus Deltochilum from nine entomological collections was reviewed. The taxonomy of the species of the subgenera Calhyboma, Hybomidium, and Telhyboma was studied. Ten species and one subspecies of the subgenera were identified and redescribed as follows: Calhyboma (D. (C.) hypponum, D. (C.) luederwaldti, D. (C.) mexicanum, D. (C.) tessellatum, D. (C.) cristinae, D. (C.) carinatum), Hybomidium (D. (H.) amazonicum, D. (H.) sp., D. (H.) lobipes, D. (H.) gibbosum panamensis) and Telhyboma (D. (T.) orbiculare). Two new species of the genus and the female of D. (Calhyboma) luederwaldti are described. D. (Calhyboma) luederwaldti and D. (Calhyboma) cristinae are new records for Colombia. The regional distribution of seven species of these three subgenera is extended. The description of the male genital organ of all the species is presented and a comparative analysis of their morphological variation is included. The elytral sculpturation of all species is presented and illustrated in detail. Only 10% of the specimens studied had been correctly identified to species. This study improved the taxonomic understanding of the genus Deltochilum in Colombia.